Profiling of ribonucleotides and deoxyribonucleotides pools in response to DNA damage and repair induced by methyl methanesulfonate in cancer and normal cells - Guo, Jian-Ru (Oncotarget, 2017)
The absolute and relative pool sizes of deoxyribonucleotides (dRNs) are essential in DNA replication fidelity, DNA damage and repair. We found in this study that although DNA damage induced by methyl methanesulfonate (MMS) seemed similar in cancer (HepG2) and normal (LO2) cells, more extensive alterations in ribonucleotides (RNs) and dRNs pools occurred in HepG2 cells indicating that HepG2 cells were more vigilant to DNA damage. After 10 h repair, RNs pools were still severely perturbed in LO2 cells. Compared to LO2 cells, deoxyribonucleotide triphosphates (dNTPs) pools in HepG2 cells elevated by more folds which could facilitate more efficient DNA repair and improve survival probability following DNA damage, although this should definitely lead to higher mutation rates. DNA repair was more efficient in HepG2 cells at S phase and it partly came to an end while DNA repair was still uncompleted in LO2 cells outside S phase. In conclusion, our results demonstrated that HepG2 and LO2 cells presented many differences in nucleotide metabolism, cell cycle checkpoints and DNA repair pathways in response to DNA damage, which could be potential targets for cancer treatment.